Rapid, noncontact, sensitive, and semiquantitative characterization of buffered hydrogen-fluoride-treated silicon wafer surfaces by terahertz emission spectroscopy - Yang, Dongxun; Mannan, Abdul; Murakami, Fumikazu; Tonouchi, Masayoshi (Light, science & applications, 2022)
Advances in modern semiconductor integrated circuits have always demanded faster and more sensitive analytical methods on a large-scale wafer. The surface of wafers is fundamentally essential to start building circuits, and quantitative measures of the surface potential, defects, contamination, passivation quality, and uniformity are subject to inspection. The present study provides a new approach to access those by means of terahertz (THz) emission spectroscopy. Upon femtosecond laser illumination, THz radiation, which is sensitive to the surface electric fields of the wafer, is generated. Here, we systematically research the THz emission properties of silicon surfaces under different surface conditions, such as the initial surface with a native oxide layer, a fluorine-terminated surface, and a hydrogen-terminated surface. Meanwhile, a strong doping concentration dependence of the THz emission amplitude from the silicon surface has been revealed in different surface conditions, which implies a semiquantitative connection between the THz emission and the surface band bending with the surface dipoles. Laser-induced THz emission spectroscopy is a promising method for evaluating local surface properties on a wafer scale. In this paper, the THz emission properties from Si wafers with different surface conditions and doping conditions have been concluded, which show the potential application of LTEM on surface estimation